CPLP-TB: a new tuberculosis transnational surveillance tool for the lusophone community - Perdigão, João (2019)
Tuberculosis (TB) remains a major health problem within the Community of Portuguese Language Speaking Countries (CPLP). Despite the marked variation in TB incidence across its member-states and continued human migratory flux between countries, a considerable gap in the knowledge on the Mycobacterium tuberculosis population structure and strain circulation between the countries still exists. To address this, we have assembled and analyzed the largest CPLP M. tuberculosis molecular and drug susceptibility dataset, comprised by a total of 1447 clinical isolates, including 423 multidrug-resistant isolates, from five CPLP countries. To make this data available to the scientific community and public health authorities we developed CPLP-TB (available at http://cplptb. ff.ulisboa.pt), an online database coupled with web-based tools for exploratory data analysis. As a public health tool, it is expected to contribute to improved knowledge on the M. tuberculosis population structure and strain circulation within the CPLP, thus supporting the risk assessment of strain-specific trends.